A new diapsid with a unique tooth structure from the Middle Triassic (Ladinian) of Germany. Issue 2 (4th March 2021) - Sobral, Gabriela; Sues, Hans-Dieter; Schoch, Rainer
ABSTRACT: The Middle Triassic was an important time in the evolutionary history of reptiles because it was during this time that many modern groups originated and initially diversified. In this context, the rich fossiliferous deposits of the Ladinian-age Erfurt Formation in southern Germany play an important role in elucidating reptilian diversity during this interval. Here we present an interesting record of a reptile with an unusual dentition. The material comprises a fragment of a left dentary. The teeth are tightly spaced and have chisel-shaped crowns, with the posterolingually extending apices abutting those of the successive teeth and forming a continuous cutting edge. Micro-computed tomography scanning of the jaw fragment revealed the teeth have expanded roots and sit on an open, shallow groove. The Meckelian canal is partially open lingually and a second canal for the inferior alveolar nerve and artery extends parallel to it. Although the preserved anatomical features of the material are insufficient for precise phylogenetic placement, the structure of the robust dentary and its teeth resembles those of some lepidosaurs and certain early Mesozoic marine diapsids. The distinctive morphology of the teeth, combined with the apparent lack of tooth wear, makes it difficult to assess their functional significance. It is interesting that extinct tetrapods with similar tooth morphologies come from strata representing freshwater and brackish-water paleoenvironments, which may serve as an additional line of evidence for future Morpho-functional assessments.